Keberterimaan Antara Teks Sumber dan Teks Sasaran - Akhmad Hairul Umam (LPPM Universitas Bina Sarana Informatika, 2018)
Acceptability of the translation is one of criteria in determining the quality of translation. The objective of this research is to describe the range of acceptability between the source and target language in the novel of Vivaldi’s Virgin written by Barbara Quick as well as to identify the translation procedure used by the translator. This research is translation study with descriptive qualitative method. While the data of research is sentences taken from both the source text and the target text containing word, phrase and sentence. From the assessment, it can be concluded that translator is capable enough to translate the sentences from the source text into the target text. A translation can be understood as a transfer of massage from one language to another. Translation is an attempt to convert from one form to another to retransmit messages from the source text to the target text. Finding of this study shows that 164 data taken randomly 110 (67%) are acceptable, 33 (20%) less acceptable, and 21 (13 %) unacceptable.